Capacidad Tecnológica y economía del conocimiento: ubicación del Perú en los rankings internacionales - Ponce Vega, Luis (2018)
In the past three decades, mankind has been exposed to countless technological changes that have transformed the industry, the economy and society. To join Peru to the ongoing digital revolution, it is required to adopt measures that include the academy, business and government to enhance our technological capacity, applied research and organized scientific activity, as well as a top educational system, because in these areas, industrial and postindustrial societies, together with research and development management, produce most potential productive knowledge. However, to spark a broad national support to this goal, requires a previous knowledge about the fundamentals (and implications) of the complex ongoing process, namely: What is the nature of technical change and what are its main features? What are the main models of interpretation of this process? In which position is placed Peru in the international rankings, and to what group of countries has joined? This paper attempts to answer these questions.